Effectiveness of Land Registration for Former Customary Land Rights in Temanggung Regency - Lestari, Leli Uji; Widayati, Widayati (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to analyze: 1) The effectiveness of the implementation of land registration for former customary land ownership in Temanggung Regency. 2) Obstacles and solutions in the implementation of land registration for former customary land ownership in Temanggung Regency. This type of research is non-doctrinal research. The approach method in this study is a sociological juridical approach. The types of data in this study are primary data and secondary data sourced from primary, secondary and tertiary legal materials. The data collection method uses interviews and literature studies. The analysis in this study is prescriptive. The results of the study concluded: 1) The effectiveness of the implementation of land registration for former customary land ownership in Temanggung Regency has been running quite well because it is supported by a clear legal basis in the UUPA, the implementation of structured registration stages by the Land Office, and government programs such as PTSL and LARASITA which facilitate public access. Public participation in registration shows positive acceptance, although it is still influenced by the level of understanding of local law and culture, so that its effectiveness is gradual and not yet fully evenly distributed throughout the region. Based on Soerjono Soekanto's theory of legal effectiveness, the effectiveness of land registration of former customary land rights in Temanggung is influenced by five factors, namely: legal substance in the form of UUPA and its implementing regulations which serve as a normative basis, law enforcement structure through the active role of the Land Office and village officials, facilities and infrastructure in the form of PTSL and LARASITA programs, community factors with a level of legal awareness that is starting to increase although not evenly distributed, and cultural factors that indicate a shift from customary law to a more orderly national law. 2) Obstacles in the implementation of land registration of former customary land rights in Temanggung Regency are normative obstacles related to proving rights to customary land, structural obstacles in the form of limited human resources and institutional coordination, technical obstacles in land measurement and boundaries, cultural obstacles in the form of low legal awareness of the community, and economic obstacles in registration costs. The solutions taken include strengthening regulations, increasing the capacity of apparatus, utilizing digital technology, increasing legal awareness of the community, and providing registration fee subsidies. Keywords: Effectiveness; Former Customary Land Rights; Land Registration.